Religious accommodation for Muslim workers and patients in healthcare - Saidun, Salilah; Akhmetova, Elmira; Awang Abdul Rahman, Amilah (2019)
As the followers of a comprehensive religion that regulates all spheres of human life, it is common for practising Muslims to require certain religious accommodations at their workplaces or during any clinical encounter. This paper aims to identify the factors that facilitate the provision of religious accommodation in healthcare for both Muslim healthcare workers and patients, by specifically examining three issues: provision of halal food, prayer facilities, and Muslim-friendly dress codes. In this qualitative study, document analysis and secondary data analysis are conducted. Thematic analysis is conducted to identify the factors which influence religious accommodation in healthcare. The findings illustrate that the prospect of accommodating religious needs does not merely depend on the religion of the majority of the population, but on various factors, such as the country or the state where the healthcare institution is situated, the healthcare institution itself, the sections or departments within the healthcare institution, and the personnel who deal directly with healthcare personnel or patients requiring the religious accommodation. In addition, awareness, attitudes, rules and standards, and availability of resources also influence the provision of religious accommodation. The results suggest that individuals seeking religious accommodation at any institution ought to play a more active role in obtaining accommodation at various levels. Besides that, religious accommodation can be enhanced by improving knowledge, attitude, standards, regulations, and availability of resources in healthcare institutions.